Factors associated with tracheostomy decannulation in patients with severe traumatic brain injury. (2nd July 2020) - Jenkins, Ryne; Badjatia, Neeraj; Haac, Bryce; Van Besien, Richard; Biedlingmaier, John F.; Stein, Deborah M.; Chang, Wan-Tsu; Schwartzbauer, Gary; Parikh, Gunjan; Morris, Nicholas A.
ABSTRACT: Objective: To assess variables associated with decannulation in patients with traumatic brain injury (TBI). Participants: 79 patients with TBI requiring tracheostomy and ICU admission from January 1 st to December 31 st, 2014. Design: Retrospective analysis. Measures: Patients decannulated prior to 90 days were compared with patients who remained cannulated. Two Cox Proportional Hazards models were used to predict decannulation using variables prior to tracheostomy and throughout hospitalization. Results: Median time to decannulation was 37 days (Interquartile Range [IQR] 29–67). Variables prior to tracheostomy associated with decannulation included diabetes (HR, 0.15; 95% CI, 0.03–0.84; p =.03), craniotomy (HR, 0.25; 95% CI, 0.06–1.02; p =.05) and acute kidney injury (AKI) (HR, 0.06; 95% CI, 0.01–0.48; p =.01). Variables present throughout hospitalization included age (HR, 1.12; 95% CI, 1.01–1.21; p =.03), ventilator days (HR, 0.74; 95% CI, 0.57–0.95; p =.02), reintubation (HR, 0.07; 95% CI, 0.01–0.64; p =.02), aspiration (HR, 0.01; 95% CI, 0.0–0.29, p =.01), craniotomy (HR, 0.004; 95% CI, 0.0–0.39; p =.02) and AKI (HR, 0.0; 95% CI, 0.0–0.21; p =.01). Conclusion: The presence of diabetes, craniotomy and acute kidney injury may inform the conversation surrounding chances for decannulation prior to tracheostomy.